The Effects of Prenatal Maternal Stress on Early Temperament: The 2011 Queensland Flood Study. Issue 5 (June 2017) - Simcock, Gabrielle; Elgbeili, Guillaume; Laplante, David P.; Kildea, Sue; Cobham, Vanessa; Stapleton, Helen; Austin, Marie-Paule; Brunet, Alain; King, Suzanne
ABSTRACT: Objective: This study examined the effects of disaster-related prenatal maternal stress on infant temperament and whether the sex of the infant or the timing of the stressor in pregnancy would moderate the effects. Methods: Mothers' objective experiences of a sudden-onset flood in Queensland, Australia, their subjective emotional reactions, and cognitive appraisal of the event were assessed. At 6 months postpartum, 121 mothers reported their infant's temperament on the 5 dimensions of the Short Temperament Scale for Infants. Results: When controlling for postnatal maternal factors, subjective prenatal maternal stress and cognitive appraisal of the disaster were associated with easier aspects of infant temperament. However, several interesting interactions emerged showing negative effects of the flood. With higher levels of objective hardship in pregnancy, boys (but not girls) received more irritable temperament ratings. When the flood occurred early in pregnancy, higher levels of objective hardship predicted more arrhythmic infant temperament. Finally, mothers whose emotional response to the flood exceeded the hardship they endured reported significantly more active-reactive infants. Conclusion: Prenatal maternal stress from a natural disaster predicted more difficult temperament ratings that were moderated by infant sex, timing of the flood in gestation, and mother's emotional response to the disaster.